Opiliones are no longer the same—on suprafamilial groups in harvestmen (Arthropoda: Arachnida) - Kury, Adriano B. (Zootaxa, 2015)
A review of the names used in the arachnid order Opiliones above superfamily level is presented. Many historical branching patterns of Opiliones (for five terminals), of Laniatores (for six terminals), and of Cyphophthalmi (for six terminals) are extrapolated, compared and graphically displayed. For the first time a historical review is made of the circumscriptions of those names and comparisons are drawn to current usage. Critical clades are used as terminals and represented by the oldest valid generic name of each. Comments are made on the variant usage for 25 suprafamilial names from the literature. Cladistic definitions are provided for these names under relevant hypotheses of phylogeny. It is noted that virtually all important suprafamilial names in Opiliones changed concept over time, and the purpose of this project is to clarify the original usage compared to current, and to add historical perspective. Two options are considered for higher-level nomenclature in Opiliones: (1) a circumscriptional option, sticking to the original inclusion of the names; (2) an inertial option, where no name has priority, and follows recent use in the literature. As there is no priority for names not regulated by ICZN, option 2 prevails, because it entails massive momentum. The following new names are introduced as unranked taxa to define clades under different hypotheses of phylogeny: Tricospilata (= Triaenonychidae + Grassatores), Lomaniatores (Laniatores in the restricted sense used by Loman/Pocock), and Eulaniatores (Laniatores excluding the bizarre Synthetonychiidae). Some of the hypotheses implied by these names are conflicting and mutually exclusive, but the state of knowledge of harvestman taxonomy is quickly changing, and no hypothesis that clearly supersedes the others can be detected.